(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Ushbu maqolada tillarni o'qitish metodikasi sifatida kredit modul tizimi muhokama qilinadi. Maqolada ushbu tizimning moslashuvchanlik, moslashtirish va talabalar uchun o'rganish ustidan ko'proq nazorat qilish kabi afzalliklarini ta'kidlangan. Izohda kredit moduli tizimining afzalliklari, jumladan, talabalar motivatsiyasi va faolligini oshirish, tilni bilish darajasini har tomonlama va toʻgʻri baholash hamda iqtisodiy samaradorlikni taʼminlash imkoniyatlari taʼkidlab o‘tilgan. The provided text discusses the credit module system as a method of teaching languages. It highlights the advantages of this system, such as flexibility, customization, and greater control over learning for students. The annotation emphasizes the benefits of the credit module system, including its potential to enhance student motivation and engagement, provide a comprehensive and accurate assessment of language proficiency, and offer cost-effectiveness. It also addresses the challenges associated with this system, such as the need for ensuring a well-rounded language education, maintaining consistency and quality across different language courses, and addressing the potential lack of structure and guidance for certain students.